Students' Conceptual Understanding and Critical Thinking Skills Through Online Learning Using a Virtual Laboratory - Nanda Safarati; Rajo Hasim Lubis (STKIP Singkawang, 2022)
This study aims to analyze the understanding the concepts and critical thinking skills of physics students in online learning using a virtual laboratory. This study uses a causal associative relationship between variables. The subjects in this study consisted of 40 students from Muslim universities and Medan state universities who were programming physics laboratory courses. The sample collection technique uses random sample sampling. The instrument used in this study was a questionnaire to determine student responses to online learning using a virtual laboratory and student worksheets (LKM) to measure students' understanding of concepts and critical thinking skills. Based on the results of data analysis, it shows that online learning using virtual laboratories affects students 'understanding of concepts and critical thinking skills, with a significant value of understanding concepts and students' critical thinking skills of 0.000 <0.05, the correlation value of understanding concepts 81% and critical thinking skills of 84%. is in the very good category, so it can be concluded that there is a significant relationship between online learning using a virtual laboratory on students' conceptual understanding and critical thinking skills.